Knowledge and attitudes towards concussion in western province Rugby Union senior club rugby players - Kraak, W.; Coetzee, L.; Kruger, A.; Stewart, R.; van Vuuren, H. (International Journal of Sports Medicine, 2019)
Concussion is a frequently occurring injury in rugby which is not usually reported to coaches or medical staff. Recognition and treatment of concussion should be a priority; however, education surrounding concussion knowledge and attitudes of the players have been lacking. The aim of this study was to investigate the knowledge and attitudes toward concussion in Western Province Rugby Union (WPRU) Super League senior club rugby players. This study focused on gathering quantitative information from WPRU club rugby players, using the Rosenbaum Concussion Knowledge and Attitudes Survey-Student Version (RoCKAS-ST). The correlation between the Concussion Attitude Index (CAI) and Concussion Knowledge Index (CKI) was (r=0.14). The CKI average for the players was (16.72±2.96). The participants answered 67% (16.72±2.96) of the CKI questions and 62% (46.54±5.75) of the CAI questions correctly. The participants demonstrated sufficient knowledge of concussion, as well as safe attitudes toward concussion. A small number of players lacked knowledge of symptoms and attitudes toward concussion, which may have been influenced by the importance of games. Overall, the participants in this study demonstrated superior knowledge and safe attitudes compared to other studies. The current study found that the players had good knowledge and safe attitudes regarding the severity of concussion.